Opportunities of Designing and Using the Money Circulation Balance - Hristov, Metodi (UNWE Yearbook, 2005)
The present study is dedicated to the necessity for expanding research and experiments in line with the increasing role of money in the globalizing economy. It is based upon the conclusion that at the present moment there are no reliable instruments for macroeconomic cover and presentation of the objectively existing money circulation, together with the fact that part of the theoretical and practical problems related to this circulation is not solved.The first part of the study examines the opportunities of designing a money circulation balance. It highlights the following issues:The theoretical fundamentals of this balance, including: the opportunities of using accounting principle of double entry of money flow, the necessity for aggregating economic agents, the need for identification of money flows within aggregate Мз and the opportunities of information providing of balance;The patterns of money circulation balance, presented through a brief historical review starting from the well-known “economic  table” of Fr. Cane and ending with the established “national accounts” in order to reach the conclusion that a dynamic matrix balance of money circulation should be constituted; andThe information providing of the suggested balance through analysis of the existing opportunities together with a proposal for realization through adapting the widely used not only in Bulgaria, but also worldwide accounting standard №7 Money Flows Statement. The second part of the study is dedicated to the use of the offered dynamic matrix balance of money circulation. Specific examples illustrate the opportunities of using it for:conducting a more efficient and adequate monetary policy, consistent with both the demand for money and the influence of money circulation on the issue result/change in money supply; the change in money supply may take the form of an increase in money stock, withdrawal of money from circulation and/or preserving money stock unchanged;more precise determination of money velocity through the number of its turnovers while using the aggregate of all money flows instead of the Gross Domestic Product;enrichment of vertical and horizontal structural analysis of money circulation;tracing chain dependencies between money flows within the money circulation and their influence on money supply on the basis of an example linked to a change in corporate income taxation and creation of matrix of coefficients that helps in formulating respective prognostication balances after the total amount of money circulation has been forecasted.In conclusion, the present study suggests that future research and implementation of the suggested pattern for money circulation balance can be accomplished either by the Bulgarian National Bank or by the National Statistics Institute.